Waves of autocratization and democratization: a rejoinder. Issue 6 (18th August 2021) - Boese, Vanessa A.; Lindberg, Staffan I.; Lührmann, Anna
ABSTRACT: This is a response to Luca Tomini's "Don't think of a wave!" and Svend-Erik Skaaning's "Waves of autocratization and democratization". With this rejoinder we make three arguments: First, the question how global waves shape autocratization processes and regime transformations is now more urgent than ever. Since 1994, civil liberties and political rights of one third of the global population have been substantially and increasingly reduced due to autocratization. Second, waves of any concept can only be studied meaningfully if the underlying concepts as well as the waves are clearly defined. We argue that the conceptualization of episodes of regime transformations (ERT) in the ERT dataset provides exactly such a clear state-of-the-art empirical mapping of processes of democratization and autocratization at the national level. In addition, we highlight how our conceptualization of waves builds upon Huntington, 1993. It even improves upon it by allowing for overlap and modelling it closer to its real world counterpart. Third, we view the present debate as a prime example of fruitful scholastic argument. Ultimately, this is what will generate a better understanding of global trends of democratization and autocratization.